Paleolatitudes of Late Triassic radiolarian cherts from Argolis, Greece: Insights on the paleogeography of the western Tethys - Muttoni, G.; Tartarotti, P.; Chiari, M.; Marieni, C.; Rodelli, D.; Dallanave, E.; Kirscher, Uwe (2015)
The Hellenides fold-and-thrust range comprises two subparallel ophiolite belts of Triassic to Jurassic age – the external ophiolite belt (e.g., Mirdita, Pindos, Argolis) in the west, and the internal ophiolite belt in the east – broadly separated by the continental crust units of the Korabi–Pelagonian Zone. It is still a matter of debate whether these ophiolites derived from a single ocean (Meliata–Maliac–Vardar) or mark the suture of two distinct oceanic seaways (Pindos and Meliata–Maliac–Vardar). We contribute to the resolution of this controversy by studying the Migdalitsa Ophiolitic Complex in Argolis (Greece), which contains Triassic oceanic basalts and pertains to the external (western) ophiolite belt. Three key areas were mapped and several sites were targeted for structural, biostratigraphic, and paleomagnetic analyses. Radiolarian cherts in primary or tectonic contact with oceanic basalts were dated to the Late Triassic (Carnian–Norian) using radiolarians, and provided paleomagnetic directions of primary origin carried by magnetite and hematite. The derived mean direction was corrected for sedimentary inclination shallowing and yielded a paleolatitude of ~ 22°N that was placed in a broader paleogeographic context by reconstructing Pangea at ~ 225 ± 5 Ma using a recent apparent polar wander path corrected for sedimentary inclination shallowing.The Late Triassic paleogeography of the Tethys Ocean was constrained using additional paleolatitude estimates from the literature, which we checked and corrected (when possible) for sedimentary inclination shallowing. According to our reconstruction, the Meliata–Maliac–Vardar Ocean between Adria – the promontory of Africa – and Europe represents the locus of origin of the Late Triassic Argolis ophiolitic rocks of the external ophiolite belt, presently resting in tectonic contact on the Pindos–Subpelagonian zones, which represent a deep-water trough with no substantial evidence of in situ oceanization in the Triassic.